Chế tạo vật liệu hấp thụ H2S dạng viên đùn từ ZnO hoạt tính. - Quang và cộng sự, Vũ Thanh (Vietnam Journal of Chemistry, 2014)
A simple and effective method for producing zinc oxide active and desulphurisation absorbent is disclosed. The zinc oxide is prepared by applying ammonia-ammonium carbonate method to possess a specific surface area of 23 - 43 m2/g, bulk density of 0.12 - 0.60 g/cc and Hydrogensulfide absorption capacity of 25 - 35 g H2S/100 g ZnO. A technique procedure for preparing desulphurisation absorbent in form of two hole extrusive pellet have also been introduced. The absorbent is able to take up 19.1 - 21.3 g H2S/100 g pellets at room temperature and it can remove hydrogen sulfide from various feed gases at higher temperature.